Analisis Implementasi Kebijakan Wajib Belajar 9 Tahun dalam Meningkatkan Mutu Pendidikan di Kota Ternate - Wahyudi Barmawi; Suranto Suranto (Universitas Muhammadiyah Yogyakarta, 2016)
Education is very effective to build nation and country with dynamic civilization. Government Regulation number 47 of2008 on compulsory education is intended to realize acceleration and even distribution of education to all directionwith central and local government commitment. This research discusses implementation of 9 year compulsory educationpolicy in Ternate and factors affecting the implementation. The research was intended (1) to identify implementationof 9 year compulsory education policy in improving educational quality in state primary school and state juniorhigh school in Ternate and (2) to identify factors affecting implementation of 9 year compulsory education policy inimproving educational quality in state primary school and state junior high school in Ternate. Theory used in thisresearch is policy implementation refereeing to Grindle and Edward III views. This research used descriptive qualitativeapproach. The results show that implementation of compulsory education program in Ternate has not been optimalyet. It is indicated with attitude of policy executor in education office of Ternate in responding problems occurring inschools. There are many non-permanent employees in some school, one building for two school and library in SMPN12 in Moti Island that was hit by abrasion have not been fixed. Conclusion of the research indicated that implementationof compulsory education program in Ternate has not been optimal yet. Factor affecting compulsory educationpolicy is disposition. The disposition factor determines 9 year compulsory education policy in Ternate.